Analisis dan Perancangan Sistem Informasi Layanan Corporate Social Responsibility (CSR) pada PT. Rimba Hutani Mas - Baharsyah, Bastomi; Mulyono, Herry (Jurnal Manajemen Sistem Informasi, 2020)
CSR (Corporate Social Responbility) is a concept or action carried out by the company as a form of socialresponsibility or the environment in which the company is located. While the definition of CSR according tothe World Business Council on Sustainable Development is a commitment of businesses/companies to behaveethically and contribute to sustainable economic development, while improving the quality of life ofemployees and their families, the local community and society at large. PT. Rimba Hutani Mas., this activitycan be done in a way, how to deliver the proposal to the company, in the activities of this society must often –often a visit to the company to know the proposals approved or not. The purpose of this research is analyzingand designing information systems-based CSR Website. Penelitia generates a protopipe also in hope tocommunities and companies can facilitate yield information as soslusi to problems – problems that exist.Key-word : web, CSR, Social